Analysis of conventional energy supply resource diversity. (5th October 2015) - Nie, Pu-yan
Abstract: This article highlights the diversity of conventional energy supply resources. By economic methods, some interesting conclusions are reached. Firstly, we find that energy supply shocks yield energy diversity and high energy price. Secondly, we show that energy supply shocks reduce both consumer surplus and producer surplus. Finally, some policy implications about energy supply resource diversity are suggested to improve energy security. Highlights: This article highlights the diversity of conventional energy supply resources. Energy supply shocks yield energy diversity and high energy price. Energy supply shocks reduce both consumer surplus and producer surplus. Some policy implications are suggested to improve energy security.